The Influence of Motivation On Employee Productivity at PT. Telkom Tbk. Makassar Branch - Muhammad Junaid Kamaruddin (Economic, Management, Business and Accountancy International Journal, 2024)
This study aimed to analyze the effect of motivation on employee performance at PT. Telkom Tbk. branch Makassar in 2012, in terms in aspects of external and internal motivation. The data were obtained from the presentation of data from the respondents (questionnaire), and the results of other studies that relefan with the object studied, in this case the primary data from the telecomucation company, PT. Telkom Tbk. Branch Makassar. The statistical analysis used in this study is multiple regression analysis using SPSS 18. The findings of this study suggest that the motivation variable consisting of external motivation and internal motivation simultaneously (together) and significantly effect on the productivity of employees in PT. Telkom Tbk. In 2012. This is evidenced by the results of the F test with a significance level below 0.05. External and internal motivation variable are partially and significantly effect on the productivity of the employees. This is evidenced by the results of the t test, independent variables are affect each dependent variable if the significance level below 0.05. External Motivation with a significance level of 0.037 and Internal Motivation with significance level of 0.048 The Most dominant vanable affecting employee productivity is external motivation. This is evidenced by the Beta coefficient of external motivation greater than the internal motivation that is equal to 0522.